Interpretação e aplicação das multas de ofício, de ofício qualificada, de ofício agravada e isolada - Lima Junior, João Carlos de (2017)
The object of this dissertation is the study of the federal tax penalties provided in article 44 of the law nº 9.430/96, which are hereby presented: ex-officio fine (voluntary penalty), qualified ex-officio penalty, aggravated ex-officio penalty and isolated penalty. Considering the resonant and booming jurisprudential divergence on the subject, this dissertation seeks to discuss the sanctions’ enforcement, with the purpose of demonstrating applicable criteria to interpret the facts and the norms, fulfill subsumption and to make effective its implication. The legal norm, related respectively to its sanction, was confronted with the jurisprudence of our courts, mostly administrative, which allowed us to examine the ideas herein discussed and empirically criticize the application of the penalties. To fulfill its purpose, this dissertation demonstrates the legal norm structure, focusing nevertheless on the primary sanctioning norm and its application, by means of an analysis of the interpretation of the facts (moment in which occurs the verification of the evidences, the burden and the preclusion, and the norm interpretation analysis, indicating the construction course of the purport of the legal texts. To accomplish the interpretation herein presented, it is indubitably necessary to contextualize the legal text, the role of culture and ideology, the inherent qualities of a good interpreter and the subjective effects in any interpretation. Finally, this dissertation acknowledges the importance of the “in dubio pro” taxpayer and discusses the casting vote related to the administrative process, taking in consideration the provided in article 122 of the Law nº 5.172/66, National Tax Code (CTN). In what concerns the legal norms development related to the penalties provided in the article 44, Law nº 9.430/96, it is possible to identify in this dissertation the default rules criteria of legal incidence connected to the ex-officio penalty, qualified ex-officio penalty, aggravated ex-officio penalty and isolated penalty, fulfilling and understanding, for each one of these penalties, the material, temporal, spatial, subjective (personal) and quantitative criteria. The delimitation and range of punitive norms demand the analysis of theories and principles regarding: fraud, concepts of fraud and tax evasion, third parties succession liability and liability for violation, joint liability, interest on late payment, penalty for breach of ancillary obligation, voluntary disclosure, culpability, postponement of payment, nature and function of penalties and behavior reiteration